Capturing Unstable Metallofullerenes - Fupin Liu; Alexey A. Popov (Inorganics, 2024)
Metallofullerenes are interesting molecules with unique structures and physicochemical properties. After they are formed in the arc-discharge process, they are first buried in the carbon soot, which requires solvent extraction to fish them out, normally followed by HPLC separation. In this minireview, we summarize the main procedures developed to obtain pure metallofullerenes, including well-established extraction with conventional fullerene solvents followed by HPLC (procedure (I) as well as several methods developed for isolation and purification of unstable fullerenes insoluble in conventional fullerene solvents, including chemical modification followed by dissolution (II.1), chemical functionalization during extraction followed by HPLC (II.2), and chemical functionalization of ionic EMFs after redox-extraction followed by HPLC (procedure II.3). The main focus here is on procedure II.3, for which the current status and future perspective are discussed.